Personality traits neuroticism and openness as well as early abnormal eye conditions as predictors of the occurrence of eye problems in adulthood - Cheng, Helen (Health Psychol Open, 2017)
This study set out to examine the associations between psychological, biomedical and socio-demographic factors in childhood and adulthood associated with the occurrence of self-reported eye conditions in adulthood. In total, 5706 participants with complete data on parental social class at birth, cognitive ability accessed at age 11 years, abnormal eye conditions by the age of 16 years diagnosed by medical professionals, educational qualifications obtained at age 33 years, the Big Five Factor personality traits measured at age 50 years, current occupational levels and self-reported eye conditions at age 54 years were included in the study. Logistic regression analysis showed that among all the factors examined early abnormal eye conditions, traits neuroticism and openness as well as sex were the significant predictors of self-reported eye conditions in adulthood.